Nano-modified composite gel foam inhibitor for inhibiting spontaneous combustion of coal and preparation method of nano-modified composite gel foam inhibitor
By using nano-modified composite gel foam resistor, the problem of spontaneous combustion of coal in goaf is solved. Through the combination of modified antioxidants and nano-SiO2 particles, effective inhibition of coal oxygen reaction and heat accumulation is achieved, and the resistance effect and material stability are significantly improved.
Patent Information
- Application Number
- CN202411839121.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
The main problem of coal spontaneous combustion in goaf is the coal oxygen reaction and heat accumulation caused by continuous oxygen supply, and existing materials are difficult to effectively inhibit coal spontaneous combustion.
Nanomodified composite gel foam inhibitor is used, which consists of gelling agent sodium polyacrylate, crosslinking agent konjac glue, foaming agent sodium dodecyl sulfate, foam stabilizer xanthan gum, nanosilica particles and modified antioxidant powder. Free radicals are eliminated through physical and chemical inhibition, inhibit coal oxygen reaction and reduce reaction exothermic heat.
It significantly improves the resistivity of the material, extends the solid water cooling characteristics of the foam and the space retention time, improves the stability and durability of the material, and effectively inhibits the spontaneous combustion of coal.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite inhibitor preparation, in particular to an inhibitor of nano-modified composite gel foam for inhibiting coal spontaneous combustion and a preparation method thereof. Background Art
[0002] The essential mechanism of coal spontaneous combustion involves a complex oxidation reaction between active groups in the coal body and oxygen. In this process, various elements such as free radicals, active functional groups in coal molecules, and low molecular weight compounds all play a vital role in the low-temperature oxidation reaction of coal.
[0003] The goaf is a typical porous medium, and the coal residue in it has the peculiarity of spontaneous combustion. The overlying rock strata in the goaf are under pressure, causing different degrees of fracture and bending inside the rock strata, resulting in the fragmentation of the bottom rock strata. The coal residue at the bottom of the goaf is affected by the pressure of the overlying rock, and the fragmented coal residue becomes a combustible with a tendency to spontaneous combustion. Due to the breaking of the coal rock mass inside the goaf, a very developed fissure-pore structure is formed, which provides physical conditions for air leakage and oxygen supply. The limited space and developed air leakage channels make the air leakage speed in some areas meet the heat accumulation conditions required for coal spontaneous combustion. Affected by the mining conditions in the goaf, the coal residue has sufficient time to complete the process of low-temperature oxidation-heat accumulation-coal spontaneous combustion.
[0004] Therefore, the spontaneous combustion of coal in goaf has significant characteristics in terms of crushing combustibles, oxygen supply, heat accumulation and reaction time. The most critical and core issue is the coal-oxygen reaction caused by continuous oxygen supply and the heat accumulation caused by a good heat storage environment. Therefore, the anti-spontaneous combustion gel foam material of coal in goaf needs to pay special attention to the rheological gelling properties of the material, the accumulation and coverage properties of the foam, the good chemical resistance, the stability of the material and the weather resistance and durability. Summary of the invention
[0005] The purpose of the present invention is to provide an inhibitor of nano-modified composite gel foam for inhibiting coal spontaneous combustion and a preparation method thereof. The nano-modified composite gel foam inhibitor is mainly composed of six components: gelling agent sodium polyacrylate, cross-linking agent konjac gum, foaming agent sodium dodecyl sulfate, foam stabilizer xanthan gum, nano-silica particles and modified antioxidant powder. The antioxidant component improves the material's resistance rate by eliminating free radicals, inhibiting the coal-oxygen reaction process, and reducing the reaction heat by physical and chemical inhibition; the gel component improves the solid water cooling characteristics of the foam and increases the spatial retention time of the foam; the foam component gives the material foam properties such as wetting, flow, and coverage; the gel improves the adhesion of the foam, the foam improves the fluidity of the gel, and the gel foam achieves the overall performance balance of the gel component and the foam component; the nano-SiO2 particle component improves the foam network skeleton structure, slows down the coarsening of the foam liquid, and improves the overall stability and durability of the material. The nano-modified composite gel foam, through its unique multi-phase and multi-component dispersed functional system, each component plays a role in a specific link in the coal spontaneous combustion process, and jointly builds a complete coal spontaneous combustion prevention and control system.
[0006] The invention provides a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion, comprising the following components: a modified antioxidant, a foaming agent, a foam stabilizer, a cross-linking agent, a gelling agent and nano-SiO2 particles.
[0007] According to the nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion provided by the present invention, the preparation method of the modified antioxidant is: adding potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone to modified bentonite, heating in a water bath for sufficient reaction to obtain an antioxidant system.
[0008] According to the nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion provided by the present invention, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is xanthan gum, the cross-linking agent is konjac gum, and the gelling agent is sodium polyacrylate.
[0009] According to the nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion provided by the present invention, the ratio of the modified antioxidant, sodium lauryl sulfate, xanthan gum, konjac gum, sodium polyacrylate and nano-SiO2 particles is 2%wt: 0.3%wt: 0.4%wt: 0.3%wt: 2.5%wt: 4%wt.
[0010] According to the nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion provided by the present invention, the mass volume ratio of the modified bentonite, potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone is 12.5g:4.7mL:11.34mL:0.315g, the concentration of the potassium persulfate initiator solution is 40g / L, the purity of the acrylic acid is 95%, and the temperature of the water bath heating is 75°C.
[0011] The present invention also provides a method for preparing the above-mentioned nano-modified composite gel foam inhibitor for inhibiting spontaneous combustion of coal, comprising the following steps: S1, adding potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone to the modified bentonite, heating in a water bath to fully react to obtain an antioxidant system; S2, taking sodium lauryl sulfate and water, stirring and mixing evenly to obtain a water-based foam; S3. Add xanthan gum, konjac gum and sodium polyacrylate in sequence to the water-based foam prepared in S2, add the antioxidant system and nano-SiO2 particles prepared in S1 while stirring, and prepare a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion.
[0012] According to the method for preparing a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion provided by the present invention, the mass volume ratio of sodium dodecyl sulfate to water in S2 is 2.5:100.
[0013] In summary, the beneficial technical effects of the present invention are: Six components of gelling agent sodium polyacrylate, cross-linking agent konjac gum, foaming agent sodium lauryl sulfate, foam stabilizer xanthan gum, nano silicon dioxide particles and modified antioxidant powder in the present invention, wherein the optimal ratio of gelling agent is 2.5%wt, the optimal ratio of cross-linking agent is 0.3%wt, the optimal ratio of foaming agent is 0.3%wt, the optimal ratio of foam stabilizer is 0.4%wt, nano SiO the optimal ratio of particle is 4%wt, and the optimal ratio of modified antioxidant is 2%wt. Different components give nano SiO the different physical and chemical structural characteristics of modified composite gel foam and the performance characteristics of preventing coal spontaneous combustion, by adding nano SiO particle and modified antioxidant, the overall stability performance and the inhibitory efficiency of gel foam are improved. Nano SiO particle modified composite gel foam has shown remarkable thermal stability, and ambient temperature has a significant impact on the half-life of gel foam. As the temperature increases, the foam half-life under different foaming multiples conditions shows a gradual downward trend, but the higher foaming multiples have relatively longer half-lives at each temperature point. Increasing the foaming multiple helps to improve the structural integrity and thermal stability of the gel foam.
[0014] The invention optimizes the key components of the modified composite gel foam of nano-SiO2 particles and modified antioxidants. The nano-SiO2 modified composite gel foam regards the modified antioxidant as the main inhibitory function carrier, and the main components are selected from materials with excellent antioxidant properties, environmental friendliness, and high cost performance.
[0015] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 It is a preparation flow chart of nano-modified composite gel foam inhibitor. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms are not directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction. Example
[0020] In this embodiment, coal is used as an example for experimental description: This embodiment provides a method for preparing a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion. The components of the inhibitor are a multi-phase multi-component dispersion system, including a foam component, a gel component and a modified antioxidant component. The specific steps are as follows: S1. Add 4.7 mL of 40 g / L potassium persulfate initiator solution, 11.34 mL of 95% pure acrylic acid and 0.315 g of tert-butylhydroquinone (TBHQ) to 12.5 g of modified bentonite, and fully react under heating in a water bath at 75°C to obtain an antioxidant (inhibitor); S2. Take 0.3%wt sodium dodecyl sulfate (foaming agent) and mix with water at a mass volume ratio of 2.5:100, and stir to obtain a water-based foam; S3. Add 0.4%wt xanthan gum (foam stabilizer), 0.3%wt konjac gum (cross-linking agent) and 2.5%wt sodium polyacrylate (gelling agent) in sequence to the water-based foam prepared in S2, and add 2%wt antioxidant system prepared in S1 and 4%wt nano-silicon dioxide particles (nanoparticles) while stirring to prepare a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion.
[0021] The flowchart of the above steps is as follows Figure 1 shown.
[0022] The sodium polyacrylate used as the gelling agent in this embodiment is usually used as a water retaining agent in the field of plant protection, and is characterized by being able to naturally degrade within about two years. According to the actual needs of underground transportation in coal mines, a gelling time between 10 and 20 minutes is usually the most ideal gelling time, and sodium polyacrylate concentrations of 2%wt, 2.5%wt and 3%wt can all meet this requirement. However, a gelling time of 15 minutes corresponding to a concentration of 2.5%wt is more suitable, which can ensure sufficient reaction time and adapt to the process requirements of machine pump pipeline transportation. Therefore, in this embodiment, the optimal gelling agent addition ratio is determined to be 2.5%wt.
[0023] The cross-linking agent konjac glucomannan used in the present embodiment is itself a kind of bionic food raw material, is widely used in food industry, as safe artificial auxiliary agent, harmless to human body and environment.When the concentration of cross-linking agent increases to more than 1%wt, gel time can be reduced to 3 minutes; And when concentration reaches more than 0.7%wt, gel time can be controlled within 10 minutes, for the on-site construction process requirement of pump pipeline delivery, when cross-linking agent concentration is 0.1%wt, 0.3%wt and 0.5%wt, gel time all meets production actual demand, particularly under the condition of 0.3%wt, gel time extends to 15 minutes, therefore, determining that the optimum concentration of cross-linking agent is 0.3%wt in the present embodiment.
[0024] The foaming agent sodium dodecyl sulfate is an organic compound that is common in the cosmetics and food industries due to its stability in aqueous solutions with a wide pH value, easy synthesis, and low price. The foaming ability of the foaming agent can be significantly improved in the concentration range of 0.1%wt to 0.2%wt, and it has excellent foaming performance. However, as the concentration of the foaming agent increases to 0.3%wt, the concentration is close to its critical micelle concentration CMC. When the concentration of the foaming agent is further increased near this critical point, the foam height does not change significantly. Therefore, in this embodiment, the optimal addition concentration of the foaming agent is determined to be 0.3%wt, which achieves the best cost-effectiveness for the best foaming effect.
[0025] The xanthan gum of the foam stabilizer is produced by fermentation with carbohydrates such as corn starch as the main raw materials and is usually used as a food additive. Before the foam stabilizer concentration reaches 0.4%wt, the half-life of the foam is positively correlated with the concentration growth of the foam stabilizer; when the concentration exceeds 0.4%wt, the foam half-life and foaming height of the foam stabilizer are restricted by the critical micelle concentration, and the growth rate of the half-life gradually slows down. In this embodiment, the shortest ignition cycle of coal spontaneous combustion is comprehensively considered, and the optimal addition concentration of xanthan gum is determined to be 0.4%wt to achieve the optimal foam stabilization effect.
[0026] Nanoparticle is mainly composed of nano silicon dioxide, and ultrafine nanometer grade SiO is amorphous white powder, nontoxic, tasteless, pollution-free, water-insoluble inorganic chemical material.Nano-SiO The addition ratio of particle has a remarkable influence on the initial foam height of whipping agent, and in 1~3% concentration range, surface tension remains on more than 20mN / m, reaches the highest point when 4% concentration, and along with the further increase of nano-particle addition ratio, foaming ability is just seen strengthening, but when concentration exceeds 7% and then descends rapidly.Therefore, comprehensively considering and determining that 4%wt is nano-SiO in the present embodiment The best addition ratio of particle.
[0027] The inhibitor is a modified antioxidant. The modified antioxidant has better stability when the temperature rises. Its critical temperature for obvious water loss increases from 120℃, and its high temperature resistance is significantly enhanced. At the same time, the polymer colloid formed by tertiary butyl hydroquinone grafting has a stronger water molecule adsorption capacity, which improves the overall thermal stability of the modified antioxidant. In addition, the solid particles of bentonite can also enhance the cross-linking polymerization of the colloid, further improving the thermal stability of the modified composite gel foam material. It was originally used to improve the antioxidant capacity of animal and plant oils. The solid particles contained in bentonite are a natural mineral containing common elements in the soil such as silicon, aluminum and magnesium. With the increase of the addition amount of modified antioxidant, the generation of CO in the inhibited coal sample during the oxidation and heating process gradually decreases. In particular, when the addition amount of modified antioxidant reaches 2%wt, the lowest value of CO generation in the test coal sample is observed. However, when the addition amount of modified antioxidant exceeds 2%wt, the change in CO production is no longer obvious and shows only slight fluctuations. Therefore, in this embodiment, the optimal addition ratio of the modified antioxidant is determined to be 2%wt, which can effectively inhibit the oxidation of coal and minimize the generation of CO.
[0028] The main component materials used in this embodiment all have environmentally friendly characteristics. Therefore, the nano-modified composite gel foam inhibitor prepared in this embodiment is a new type of environmentally friendly composite inhibitor material.
[0029] In summary, the present invention has developed a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion, which is mainly composed of six components: gelling agent sodium polyacrylate, cross-linking agent konjac gum, foaming agent sodium dodecyl sulfate, foam stabilizer xanthan gum, nano silicon dioxide particles and modified antioxidant powder. Different components give the nano-SiO2 modified composite gel foam different physical and chemical structural characteristics and performance characteristics for preventing coal spontaneous combustion. By adding nano-SiO2 particles and modified antioxidants, the overall stability and inhibitory efficiency of the gel foam are improved.
[0030] The present invention optimizes the key components of the modified composite gel foam of nano-SiO2 particles and modified antioxidants. The nano-SiO2 modified composite gel foam regards the modified antioxidant as the main carrier of the inhibitory function, and the main components are selected from materials with excellent antioxidant properties, environmental friendliness, and high cost performance. The key chemical components are chemically modified by the intercalation grafting method to improve the material's inhibitory properties and thermal stability, and nano-silicon dioxide particles are added to enhance the gel foam network skeleton structure, which improves the overall durability and thermal stability of the gel foam.
[0031] Nano-SiO2 particle modified composite gel foam exhibits excellent thermal stability, and the ambient temperature has a significant effect on the half-life of gel foam. With the increase of temperature, the half-life of foam under different foaming multiples shows a trend of gradual decrease, but the half-life at each temperature point is relatively long for higher foaming multiples. The increase of foaming multiples helps to improve the structural integrity and thermal stability of gel foam.
[0032] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion, characterized in that: The invention comprises the following components: a modified antioxidant, a foaming agent, a foam stabilizer, a cross-linking agent, a gelling agent and nano-SiO2 particles.
2. The nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The preparation method of the modified antioxidant comprises the following steps: adding potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone into modified bentonite, and heating in a water bath to fully react to obtain the modified antioxidant.
3. The nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The foaming agent is sodium lauryl sulfate, the foam stabilizer is xanthan gum, the cross-linking agent is konjac gum, and the gelling agent is sodium polyacrylate.
4. The nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion according to claim 2, characterized in that: The ratio of the modified antioxidant, sodium lauryl sulfate, xanthan gum, konjac gum, sodium polyacrylate and nano-SiO2 particles is 2%wt: 0.3%wt: 0.4%wt: 0.3%wt: 2.5%wt: 4%wt.
5. The nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion according to claim 2, characterized in that: The mass volume ratio of the modified bentonite, potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone is 12.5g:4.7mL:11.34mL:0.315g, the concentration of the potassium persulfate initiator solution is 40g / L, the purity of the acrylic acid is 95%, and the water bath heating temperature is 75°C.
6. A method for preparing a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, adding potassium persulfate initiator solution, acrylic acid and tert-butylhydroquinone to the modified bentonite, heating in a water bath to fully react to obtain a modified antioxidant; S2, taking sodium lauryl sulfate and water, stirring and mixing evenly to obtain a water-based foam; S3, to the water-based foam prepared in S2, xanthan gum, konjac gum and sodium polyacrylate are added in sequence, and the modified antioxidant and nano-SiO2 particles prepared in S1 are added while stirring to prepare a nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion.
7. The method for preparing the nano-modified composite gel foam inhibitor for inhibiting coal spontaneous combustion according to claim 5, characterized in that: The mass volume ratio of sodium dodecyl sulfate to water in S2 is 2.5:100.
Citation Information
Cited By
Thermo-sensitive hydrogel composite inhibitor for inhibiting spontaneous combustion of coal and preparation method of thermo-sensitive hydrogel composite inhibitor
CN120819397A
Proportioning optimization and thermal stability test method of nano-composite inhibited gel foam material
CN122403847A